Advances in hyaluronic acid hydrogel for meniscus repair - Wang, Guangxin; liu, Xiao Jun; Zhang, Xin-an; Hu, Mingjie (Frontiers in Bioengineering and Biotechnology, 2025)
The meniscus, an important fibrocartilaginous structure within the knee joint, plays essential roles in shock absorption, joint stabilization, and the optimization of mechanical force transmission. Meniscus injuries are common among athletes, middle-aged and elderly individuals, and those engaged in heavy physical labor. Both conservative and surgical treatments currently have limitations, making it difficult to achieve complete repair and functional restoration of meniscal tissue. In recent years, hyaluronic acid (HA) hydrogel has shown broad potential in meniscus repair due to its excellent biocompatibility and biodegradability. As a cell carrier, this material not only promotes cell migration, proliferation, and differentiation but also mimics the biomechanical properties of the meniscus, regulates the inflammatory environment, and facilitates angiogenesis, thereby creating favorable conditions for tissue regeneration. This review summarizes the mechanisms, current applications, and research advances of HA hydrogel in meniscus repair, aiming to provide new theoretical foundations and technical support for meniscus injury treatment and to promote clinical translation and development in this field.